Analysis of soils spatial differentiation and productivity in forest management unit Muzljanski rit : Prostorna analiza tala i utjecaj na produktivnost u gospodarskoj jedinici Mužljanski rit - Galić, Zoran, inženjer šumarstva (Array, 2021)
The paper presents analysis of soil spatial distribution and productivity of Populus x euramericana I-214 forest cultures in forest management unit (hereinafter: FMU) Muzljanski rit. Soil cover in the FMU is heterogeneous in relation to position and altitude in floodplain. Analysis were conducted on eugley and humogley soil types. Eugley, soil type, was delineated according to physiologically active soil depth as α, β or β/γ gley soils and humogley was delineated as one soil unit. Cultures of the poplar clones Populus x euramericana I-214 are found on at least two but usually more different site types within the same forest management section (18.43 %). Single forest management section is a by definition a single forest spatial unit having similar ecologic factors. Aim of our research was to enable consistent forest section delineation, based on the interaction of soil productivity properties and distribution as well as Populus x euramericana I-214 productivity dataset. Based on our anaysis (spatial analysis of raster layers of soil systematic unit distribution-soil subunit, digital elevation model and productivity according to inner delineation of FMU Muzljanski rit), the resuts show eugley share in lower systematic soil unit. The results show contribution of lower systematic units of eugley in forest managemet section/culture. We found a raising trend of α and β-gley, as well as humogley. On one side the higher contribution of this sistematic units indicates reduction in the forest culture yield. On the other side higher contribution of β/γ gley indicates an increase of culture yeald. The Populus x euramericana I-214 cultures are spatialy concentrated, extending over soil units with different characteristics, pointing in alternative economicaly justified section delineation, based on the soil types.